Distance learning perceptions from higher education students — The case of Portugal - Gonçalves, S. P. (2021)
This research study examines the attitudes of Portuguese higher education students regarding compulsory digital and distance learning university courses during the second semester of the academic year 2019–2020 during the COVID-19 pandemic. The methodology was quantitative, being the undergraduate and postgraduate students surveyed to find their perceptions about distance and online education in Portugal. The findings of the study highlighted the relationship between distance and online learning. The key concern of the respondents is related to the formal and contextual dimensions of the online class regime. The values examined, taken as a whole, allow us to conclude that with this teaching regime, in terms of awareness, there is acceptance and benefit. The sense of ambiguity in which this transformation took place, as well as the climate surrounding this phase, are worth noting. The teaching and evaluation methodologies used have been embraced and show a very wide range of choices on the part of the teaching teams and the students’ various interests, just as in the teaching regime of the classroom. The fact that students feel the need for face-to-face classes, however, is of great importance for practical and laboratory classes. This reality, which is a challenge to face in the future, is hard to overcome.